PENDEKATAN STM MELALUI PENGGUNAAN APLIKASI ANDROID DALAM PEMBELAJARAN IPS DI SMP KOTA BANDUNG - Holilah, Mina -; Nur, Muhammad; Widyanti, Triani (Universitas Negeri Makassar, 2023)
Research of STM (Science, Technology and Society) approach to social studies learning has not been developed much. So far, STM has been used more in science learning. This research was designed as a positive response in facing the Industrial Revolution 4.0 which had a revolutionary impact on the education. Consistently integrated efforts are needed to develop science and technology-based learning innovations that are closely related to societal problems which are the subject of social studies. The research method used is a survey. The android application is used as a means to improve social studies learning practices in junior high schools, especially for online learning. Social studies learning activities ultimately lead to the 21st century 4C skills (Collaboration, Critical Thinking, Creativity, and Communication). Social studies learning is expected to not only equip students with knowledge, but also with the attitudes and skills that are qualified in the 21st century.